ANTIDEPRESSANT EFFECT OF SOLANUM SURATTENSE BURM. F - A. W. Khan; A.U. Khan (Journal of Animal and Plant Sciences, 2019)
Solanum surattense Burm. f. is used in traditional medicine for various health problems, including depression. This research was conducted to explore the antidepressant effect of Solanum surattense in order to validate its therapeutic use in depression. Forced swim test (FST), tail suspension test (TST) and open field test models of mice were used for the investigation of antidepressant effect of Solanum surattense crude extract (Ss.Cr) by the determination of behavioural responses of mice like swimming, climbing, immobility time, ambulations and rearings in these test models. Ss.Cr tested positive for alkaloids, flavonoids, saponins, steriods and tannins. It exhibited antidepressant effect by dose dependently (100-200 mg/Kg) decreasing immobility time (P < 0.001 vs normal saline respectively) in both FST and TST, while increased swimming duration (P < 0.01, P < 0.001 vs normal saline respectively), as exhibited by fluoxetine (20 mg/Kg). Ss.Cr did not significantly alter ambulation and rearing frequencies in open field test. SS.Cr did not produce any mortality up to 5 g/Kg dose in acute toxicity test. These results indicate that Solanum surattense possess antidepressant activity. The presence of phytochemicals, such as flavonoids and saponins argue the cogency of the proclaimed folk medicinal effect in depression.
Keywords: Solanum surattense Burm. f; Antidepressant; Forced swim test; Tail suspension test; Open field test; Mice